P268 MANAGEMENT OF ACUTE PULMONARY EMBOLISM IN THE EMERGENCY ROOM IN ELDERLY: DOES ADHERENCE TO INTERNATIONAL GUIDELINES INCREASE IN THE MOST SERIOUS CASES?. (18th May 2022) - Savioli, G; Ceresa, I; Fumoso, F; Lapia, F; Brattoli, M; Maggioni, P; Mugellini, A; Martignoni, A; Manzoni, F; Muzzi, A; Novelli, V; Preda, L; et al.
Abstract: Premises: Pulmonary embolism is a pathology still characterized by high mortality. Some international studies have actually shown that adherence to guidelines is generally quite low in both primary and secondary care and ranges, depending on the studies, between 40 and 60%. Purpose of the Study: see if and how, in the real life of an Emergency Department, adherence to the Guidelines varies according to the severity of the acute pulmonary embolism. We understood this severity as the presence of organ damage or massive pulmonary embolism. Methods: Single–center retrospective observational study, on all geriatric patients (>75 y) who entered our ED, where they received a diagnosis of acute PE. Enrollment began in 2016 and ended in 2019. We collected data from medical history, physical examination, laboratory tests, imaging; we calculated the characteristic scores from the diagnostic / therapeutic algorithm, both for the risk of PE (Wells, Geneva and Years), and for the presentation of the risk of mortality at 30 days (sPESI). We therefore analyzed adherence to the guidelines in three decisional turning points: 1 Correct application of the decision scores examined, which classify the patient at low, intermediate or high risk of PE, calculated with Wells and simplified Geneva score; 2 Correct administration of therapy starting from ED as suggested by the guidelines; 3 Any observation in the care area of medium intensity with careful monitoring for the subpopulation of patients with finding of right ventricular dilation or myocardial enzyme elevation (considered to be at high risk of shock and short–term mortality). Results: We enrolled 248 patients, with a mean age of 83 years with female prevalence (F = 62%). Of these, 81 (32.7%) have organ damage and 86 (34.7%) have massive pulmonary embolism. Patients with organ damage received treatment with a higher adherence to the guidelines (68%) than those who did not have organ damage (51%) in a statistically significant way (p < 0.01). Patients with massive pulmonary embolism received treatment with a higher adherence to the guidelines (69 %) than those with peripheral pulmonary embolism (50%) in a statistically significant way (p < 0.005). Conclusions: The study suggests that patients with organ damage or massive pulmonary embolism are more likely to receive treatment in the emergency room with greater compliance with international guidelines.